Penerapan Problem Based Learning dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMA - Sukmayanti, Mimih (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2020)
The main purpose of this research is to compare the student mathematics problem solving ability of senior secondary school (SMA) students who received problem based learning, with those who received exporitory learning. This research was based on fact that the student mathematics problem solving ability of the secondary school student in SMAN 1 Pagaden were not good enough. The method used is mix method with Concurrent Embedded Eksperimental Model with Classroom action research.The Subject in this research was SMA students from grade XI MIPA classes majoring in science, from SMAN 1 Pagaden Subang. The instrumens were: Mathematics problem solving ability test, learning motivation questionnaire, student attitude scale and observation sheet. Summaries based on the analysis were: (1) Problem Based Learning model can improve student mathematics problem solving; (2) learning motivation of students have Problem Based Learning is better; (3) Students who received Problem Based Learning model have higher mathematics problem solving ability than those who received expository learning; (4) Students who received Problem Based Learning model have higher learning motivation than those who received expository learning; (5) There is a correlation between learning motivation and student mathematics problem solving ability; (6) the activity of the students who recieved Problem Based Learning is better. In general, Problem Based Learning could be considered as one of mathematics learning alternative in order to increase student mathematics problem solving ability.